2008
DOI: 10.1038/jhh.2008.38
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of haemodynamic parameters in the recovery phase of an exercise test. The Finnish Cardiovascular Study

Abstract: We tested the hypothesis that the change from the peak to recovery values of systolic arterial pressure (SAP recovery ) and rate-pressure product (RPP recovery ) can be used to predict all-cause and cardiovascular mortality, as well as sudden cardiac death (SCD) in patients referred to a clinical exercise stress test. As a part of the Finnish Cardiovascular Study (FINCAVAS), consecutive patients (n ¼ 2029; mean age±SD ¼ 57±13 years; 1290 men and 739 women) with a clinically indicated exercise test using a bicy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…The Finnish cardiovascular study saw HR more than double with peaks during exercise of 152bpm and 131bpm during an exercise stress test. 15 Similar increases in HR were seen by Simonson and Wyatt 19 who saw HR peaks of 175bpm during supine cycle ergometry and 187bpm on a treadmill in maximum stress tests. The recovery seen after IRT occurs within 20 seconds, indicating that it is less dangerous than aerobic exercise due to low increases in heart rate and fast recovery.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The Finnish cardiovascular study saw HR more than double with peaks during exercise of 152bpm and 131bpm during an exercise stress test. 15 Similar increases in HR were seen by Simonson and Wyatt 19 who saw HR peaks of 175bpm during supine cycle ergometry and 187bpm on a treadmill in maximum stress tests. The recovery seen after IRT occurs within 20 seconds, indicating that it is less dangerous than aerobic exercise due to low increases in heart rate and fast recovery.…”
Section: Discussionsupporting
confidence: 56%
“…13,14 Rate pressure product during stress tests is also a determinant of cardiovascular mortality. 15 Despite concerns that RPP is raised during IRT, evidence suggests that during maximal isometric resistance exercise, RPP is lower than that seen during maximal aerobic exercise. 9,10 Previous studies into the effect of isometric exercise on blood pressure have not looked at peak SBP, HR and RPP during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially crucial in monitoring cardiac patients undergoing treadmill exercise tests during cardiac rehabilitation. It has been suggested that rate-pressure product (i.e., heart rate 9 systolic blood pressure) is the key monitoring parameter during this procedure (Pierson et al 2004;Nieminen et al 2008). Our objective was therefore to assess the potential use of certain cardiovascular signals (obtained non invasively) as estimators of systolic (SBP) and diastolic (DPB) blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated SBP response during the exercise anticipation phase and recovery from exercise have been related to increased risk of resting hypertension [6,20] and stroke [18], and cardiovascular mortality [25,29]. However, SBP decrease from peak exercise to recovery phase was not related to cardiovascular mortality in a previous study, although the effect of resting blood pressure compared to exercise blood pressure was not reported [30]. High SBP immediately after exercise phase may reflect the over-activity of the sympathetic nervous system and inadequate vagal reactivation as both SBP and heart rate are regulated by the autonomic nervous system [15].…”
Section: Discussionmentioning
confidence: 88%